Pemanfaatan Daun Nanas Sebagai Bahan Alternatif Filler Dalam Sintesis Komposit: Dengan Variasi Tebal Komposit Dan Persen Berat Serat - Riski Adi Mulia; Idral Amri; Yusnimar Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Composite with suitable mechanical properties were needed to meet SNI in the operation of tank in water treatment unit. Some things that can effect it were thick composites and percent weight of fiber. This research aims to make composites with natural fiber fillers from pineapple leaves, acknowledge the optimum tensile strength and flexural strength in composites with variations in composite thickness, and acknowledge the optimum tensile strength and flexural strength in composites with variations in fiber weight. In this research the material used is pineapple fiber with a fiber weight of 15%, 25%, 35%, 45%, with variations of thickness 1; 2 3 4; and 5 mm, used Polyester BQTN 157 as its matrix. Made in press mold, tensile srength tested the standard carried out with ASTM 638-02 and bending standards with the standard reference ASTM D 790-02. Tested was carried out on variations in fiber weight 15%, 25%, 35%, 45%, and variations in composite thickness 1; 2 3 4; and 5 mm . From the tests that have been carried out obtained maximum tensile strength of 63.02 MPa, at 45% by weight of fiber and 5 mm thick, while on bending testing the optimal average on fiber weight was 45% with a thickness of 1 mm which was equal to 445.50 MPa. This result was suitable with SNI for tank operation in the water treatment unit..Keywords : bending strength, tensile strength, polyester, pineapple fiber